Milt production response of the sea bass Lates calcarifer (Bloch) to luteinizing hormone-releasing hormone analogue and 17a-methyltestosterone - Garcia, Grace H. (Iloilo College of Fisheries, University of the Philippines, 1992)
Milt volume, sperm density, number of spermatozoa, and fertilization capacity were determined to quantify the milt production response of mature sea bass to LHRHa [(D-Ala6, Pro9 - N-ethylamide) LHRH in saline solution and 17a-methyltestosterone in corn oil (MT). Two measures of sperm density, sperm count andspermatocrit, were highly correlated (r=0.85). Compared with control, milt volume and the number of spermatozoa collected increased but sperm count decreased (24% at 24h) after a LHRHa (20 ug/kg body weight) treatment, suggesting a stimulation of spermatozoa production and not merely milt production. Further milt dilution (44%) was induced by 80 ug/kg LHRHa (LHRHa80) at 12 h post-treatment but not by 200 ug/kg MT (MT200) alone. a milt dilution of only 27% at 12 h after simultaneous injections of LHRHa80 and MT200 may indicate an inhibitory effect of a high MT dose on the efficiency of LHRHa. Early in the breeding season, a high fertilization capacity (857,000 egg/kg) of LHRHa80-treated male was obtained only when spawning occured in less than 12 h after hormone treatment, but no fertilization was observed when spawning occured in 30-36 h post-treatment. During the peak season and when spawing occured in 30-36 h post-treatment, a low fertilization capacity (79,000 eggs/kg) was observed in one of two LHRHa (40 ug/kg)-treated male but none in three LHRHa80-treated males. However, higher fertilization capacities (224,000-410,000 eggs/kg) in two of three males injected 100 ug/kg (MT 100) were obtained. Twards the end of the breeding season, spontaneous milt release as indicated by fertilization of eggs occured only after multiple injections of MT100. Together, these results indicate that spermazoa production, milt dilution, and spontaneous milt release can be stimulated by LHRHa or a low MT dose. The low incidence of fertilization and bvariability in fertilization capacity of hormone-treated sea bass may be due to a possible lack of synchrony in the release of gametes.
Thesis (M. S. Fisheries-Aquaculture) - University of the Philippines in the Visayas, April 1992.
Keywords: Sea basses; Lates calcarifer Bloch